2021
DOI: 10.3390/nu13093208
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Interventions on Chronic Inflammatory Diseases in Relation to the Microbiome: A Systematic Review

Abstract: Chronic inflammation plays a central role in the pathophysiology of various non-communicable diseases. Dietary interventions can reduce inflammation, in part due to their effect on the gut microbiome. This systematic review aims to determine the effect of dietary interventions, specifically fiber intake, on chronic inflammatory diseases and the microbiome. It aims to form hypotheses on the potential mediating effects of the microbiome on disease outcomes after dietary changes. Included were clinical trials whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 112 publications
1
40
0
4
Order By: Relevance
“…In this context, change in dietary habits is one of the most powerful ways to alter the gut microbiome [ 208 , 209 ]. For instance, high-fiber diets (e.g., vegetarian, vegan, Mediterranean), which are low in red meat and higher in unsaturated fatty acids, are associated with a more beneficial microbiome composition, an increased microbial diversity, and more health-promoting bacteria (e.g., Bifidobacteria , Lactobacillus ), as well as higher levels of small chain fatty acids (especially butyrate) [ 210 , 211 , 212 , 213 ].…”
Section: Discussion and Therapeutic Perspectivesmentioning
confidence: 99%
“…In this context, change in dietary habits is one of the most powerful ways to alter the gut microbiome [ 208 , 209 ]. For instance, high-fiber diets (e.g., vegetarian, vegan, Mediterranean), which are low in red meat and higher in unsaturated fatty acids, are associated with a more beneficial microbiome composition, an increased microbial diversity, and more health-promoting bacteria (e.g., Bifidobacteria , Lactobacillus ), as well as higher levels of small chain fatty acids (especially butyrate) [ 210 , 211 , 212 , 213 ].…”
Section: Discussion and Therapeutic Perspectivesmentioning
confidence: 99%
“…A study of 60 patients with IBD showed improved symptom scores and fecal calprotective protein in the low-FODMAP diet subgroup compared to the SD ( Bodini et al, 2019 ). Mediterranean diets, diets high in fruits, vegetables, and other plant foods, as well as high-fiber diets (including fiber supplementation) are associated with reduced levels of inflammation ( King et al, 2007 ; Smidowicz and Regula, 2015 ; Wagenaar et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota collaborates with the host’s immune system to prevent disease colonization, gut infiltration from pathogens, and intestinal epithelial damage [ 48 ]. Digestion, metabolite synthesis, and immune system conditioning are all aspects of the microbiome that help modify inflammatory processes [ 49 ]. The variety and quantity of bacterial species can vary dramatically depending on various circumstances, including health state, with a microbiome with a higher diversity of microorganisms associated with better health [ 49 ].…”
Section: High-fiber Diet For Ibd: What We Knowmentioning
confidence: 99%